# partial sums

• Apr 9th 2011, 09:01 PM
Random Variable
partial sums
Let $\displaystyle \displaystyle \sum_{n=0}^{\infty} a_{n} x^{n}$ be a convergent series.

Let $\displaystyle S_{n}$ be the nth partial sum of the above series.

Then $\displaystyle \displaystyle \sum^{\infty}_{n=1} S_{n} x^{n} = \frac{1}{1-x} \sum^{\infty}_{n=0} a_{n} x^{n}$ .

Should this be obvious? I don't get it.
• Apr 9th 2011, 09:08 PM
Prove It
It might help to note that $\displaystyle \displaystyle \frac{1}{1 - x} = \sum_{n = 0}^{\infty}x^n$...
• Apr 9th 2011, 09:35 PM
Random Variable
$\displaystyle \displaystyle \sum_{n=0}^{\infty} S_{n} x^{n} = \sum^{\infty}_{n=0} \sum^{n}_{k=0} (a_{k}x^{k}) x^{n}$

Reverse the order of summation?
• Apr 9th 2011, 11:08 PM
Random Variable
It makes sense when you write out the terms.

$\displaystyle \displaystyle \frac{1}{1-x} \sum^{\infty}_{n=0} a_{n} x^{n} = \frac{a_{0} + a_{1} x + a_{2}x^{2} + ...}{1-x}$

$\displaystyle \displaystyle = (a_{0} + a_{1} x + a_{2}x^{2} + ...)(1 + x + x^{2} + ...) \ , \ \text{for} \ |x| < 1$

$\displaystyle \displystyle= a_{0} + (a_{0}+ a_{1}) x + (a_{0}+a_{1}+a_{2}) x^{2} + ...$

$\displaystyle \displaystyle = \sum^{\infty}_{n=0} S_{n} x^{n}$
• Apr 9th 2011, 11:16 PM
Drexel28
Quote:

Originally Posted by Random Variable
Let $\displaystyle \displaystyle \sum_{n=0}^{\infty} a_{n} x^{n}$ be a convergent series.

Let $\displaystyle S_{n}$ be the nth partial sum of the above series.

Then $\displaystyle \displaystyle \sum^{\infty}_{n=1} S_{n} x^{n} = \frac{1}{1-x} \sum^{\infty}_{n=0} a_{n} x^{n}$ .

Should this be obvious? I don't get it.

I think you're overthinking this, by definition assuming all the proper conditions are met the Cauchy Product says that $\displaystyle \displaystyle \sum_n x^n\sum_n a_n x^n=\sum_n (\sum_{k=0}^n a_k 1)x^n$